Implementing Islamic Character Values of Social and Environmental Care at MTs Darul Huda Mayak Ponorogo: A Qualitative Study - Prajoko, Indra; Humaedah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Abstract: This study explores the implementation of character values centered on social and environmental care from an Islamic perspective at MTs Darul Huda Mayak Ponorogo. Utilizing a qualitative research methodology grounded in post-positivist philosophy, the research involved participant observation, in-depth interviews, and document analysis to gather data. The findings indicate that Islamic teachings significantly shape the school's approach to character education, emphasizing principles of social responsibility and environmental stewardship. Routine activities, spontaneous actions, role modeling, and school-wide initiatives are designed to teach these values. The study reveals a holistic integration of Islamic values into the school culture, highlighting the effectiveness of this approach in fostering social and environmental consciousness among students. While the research provides valuable insights into the role of Islamic education in character development, its focus on a single institution and qualitative nature may need to be revised in generalizability. Future research should consider diverse educational contexts and employ quantitative measures to assess the long-term impact of these programs. Abstrak: Penelitian ini mengeksplorasi implementasi nilai-nilai karakter yang berfokus pada kepedulian sosial dan lingkungan dari perspektif Islam di MTs Darul Huda Mayak Ponorogo. Menggunakan metodologi penelitian kualitatif yang berlandaskan filosofi post-positivis, penelitian ini melibatkan observasi partisipan, wawancara mendalam, dan analisis dokumen untuk mengumpulkan data. Temuan menunjukkan bahwa ajaran Islam secara signifikan membentuk pendekatan sekolah terhadap pendidikan karakter, dengan menekankan prinsip-prinsip tanggung jawab sosial dan kepedulian terhadap lingkungan. Kegiatan rutin, tindakan spontan, keteladanan, dan inisiatif sekolah secara keseluruhan dirancang untuk mengajarkan nilai-nilai tersebut. Penelitian ini mengungkapkan integrasi nilai-nilai Islam secara holistik dalam budaya sekolah, yang menyoroti efektivitas pendekatan ini dalam menumbuhkan kesadaran sosial dan lingkungan di kalangan siswa. Meskipun penelitian ini memberikan wawasan yang berharga tentang peran pendidikan Islam dalam pengembangan karakter, fokusnya pada satu institusi dan sifat kualitatifnya mungkin membatasi generalisasi. Penelitian selanjutnya disarankan untuk mempertimbangkan konteks pendidikan yang beragam dan menggunakan ukuran kuantitatif untuk menilai dampak jangka panjang dari program-program ini.